Zero-index metamaterial superstrates uwb antenna for microwave imaging detection - Mohd Aminudin, Jamlos; Nur Amirah, Othman; Wan Azani, Mustafa; Mohd Faizal, Jamlos; Mohamad Nur Khairul Hafizi, Rohani (Tech Science Press, 2023)
Metamaterials (MTM) can enhance the properties of microwaves and also exceed some limitations of devices used in technical practice. Note that the antenna is the element for realizing a microwave imaging (MWI) system since it is where signal transmission and absorption occur. UltraWideband (UWB) antenna superstrates with MTM elements to ensure the signal transmitted from the antenna reaches the tumor and is absorbed by the same antenna. The lack of conventional head imaging techniques, for instance, Magnetic Resonance Imaging (MRI) and Computerized Tomography (CT)scan, has been demonstrated in the paper focusing on the point of failure of these techniques for prompt diagnosis and portable systems. Furthermore, the importance of MWI has been addressed elaborately to portray its effectiveness and aptness for a primary tumor diagnosis. Other than that, MTM element designs have been discussed thoroughly based on their performances towards the contributions to the better image resolution of MWI with detailed reason-ings. This paper proposes the novel design of a Zeroindex Split Ring Resonator (SRR) MTM element superstrate with a UWB antenna implemented in MWI systems for detecting tumor. The novel design of the MTM enables the realization of a high gain of a superstrate UWB antenna with the highest gain of 5.70 dB. Besides that, the MTM imitates the conduct of the zeroreflection phase on the resonance frequency, which does not exist. An antenna with an MTM unit is of a 7 × 4 and 10 × 5 Zero-index SRR MTM element that acts as a superstrate plane to the antenna. Apart from that, Rogers (RT5880) substrate material is employed to fabricate the designed MTM unit cell, with the following characteristics: 0.51 mm thickness, the loss tangent of 0.02, as well as the relative permittivity of 2.2, with Computer Simulation Technology (CST) performing the simulation and design. Both MTM unit cells of 7 × 4 and 10 × 5 attained 0° with respect to the reflection phase at the 2.70 GHz frequency band. The first design, MTM Antenna Design 1, consists of a 7 × 4 MTM unit cell that observed a rise of 5.70 dB with a return loss (S11) −20.007 dB at 2.70 GHz frequency. The second design, MTM Antenna Design 2, consists of 10 × 5 MTM unit cells that recorded a gain of 5.66 dB, having the return loss (S11) −19.734 dB at 2.70 GHz frequency. Comparing these two MTM elements superstrates with the antenna, one can notice that the 7 × 4 MTM element shape has a low number of the unit cell with high gain and is a better choice than the 10 × 5 MTM element in realizing MTM element superstrates antenna for MWI.